The sound of the suburbs: noise from out of nowhere? (2013)
From hip hop’s urban violence and anti-police messages to earlier examples, for example the Jam’s ‘In the City’ there has been an abiding pop fascination with urban imagery in pop and denigration of the suburb, as seen on the Sex Pistols’ track ‘Satellite’ in which Rotten snarls ‘I don’t like where you come from/It’s just a satellite of London.’ Nonetheless there is a rich vein of pop documenting post-war suburbia on both sides of the Atlantic dating from 1960s beat combos, through 1970s punk via Th e Pet Shop Boys in the 1980s with their single ‘Suburbia’ and 1990s grunge up to the award-winning 2010 album by Canadian indie outfi t Arcade Fire Th e Suburbs . In tone these have oscillated between a commiseration of suburban drudgery and a celebration of the periphery and its possibilities. Pop has long had a centrality in post-war youth culture off ering escape routes to its practitioners and to its listeners, alternatives to their routine surroundings in the form of emotional escapism. Th e suburbs have not only been spaces where pop music is listened, to or consumed but it has also been the inspiration and locale in which much pop was created or produced. Pop’s practitioners frequently have been drawn from suburban locations which have provided much impetus to pop’s messages and meanings. It has both refl ected the suburban surroundings of its creators and provided a soundtrack for its suburban listeners whose lives were played out in box bedrooms at the edges of cities. Th e signifi cance of place and its relationship to popular music at large is a growing area of academic enquiry. Socio-spatial interest in pop soundtracks appears to have intensifi ed in an era of increased globalization within the music industry: perhaps because of the inescapable pull of such tendencies. Studies concentrating on the signifi cance of the ‘local’ usually in music-making have included those of Bennett ( 2000 ), Finnegan ( 1989 ) and Forn ä s and Lindberg ( 1995 ) but each concentrated on their own locales rather looking at the broader category of suburbia. Th is chapter attempts to address this imbalance by looking at the fi eld of suburban pop and how music has refl ected multiple suburbias and how in tone it has shift ed from optimism to ennui.